Enhanced nanoparticle uptake into virus infected cells: could nanoparticles be useful in antiviral therapy? - Abo-zeid, Yasmin; Urbanowicz, Richard A.; Thomson, Brian J.; Irving, William L.; Tarr, Alexander W.; Garnett, Martin C. (Elsevier, 2018)
Virus infections cause diseases of different severity ranged from mild infection e.g. common cold into life threatening diseases e.g. Human Immunodeficiency virus (HIV), Hepatitis B. Virus infections represent 44% of newly emerging infections. Although there are many efficient antiviral agents, they still have drawbacks due to accumulation at off target organs and developing of virus resistance due to virus mutation. Therefore, developing a delivery system that can selectively target drug into affected organs and avoid off target accumulation would be a highly advantageous strategy to improve antiviral therapy. Nanoparticles (NP) can be effectively targeted to the liver, and therefore it could be used for improving therapy of hepatic virus infections including hepatitis B virus and hepatitis C virus (HCV). Many studies were performed to encapsulate antiviral agents into nano-delivery system to improve their pharmacokinetics parameters to have a better therapeutic efficacy with lower side effects. However, the effect of virus infection on the uptake of NP has not yet been studied in detail. The latter is a crucial area as modulation of endocytic uptake of nanoparticles could impact on reduce potential therapeutic usefulness of antiviral agents loaded into nano-delivery system. In this study, a fluorescently-labelled polymeric nanoparticle was prepared and used to track NP uptake into Huh7.5, human hepatoma cells transfected with replicating HCV genomes, compared with non-transfected cells as a model representing hepatocyte uptake. Confocal microscopy and flow cytometry of virus transfected Huh7.5 cells unexpectedly demonstrated two-fold increase in uptake of NP compared to non-transfected cells. Therefore, virus transfection enhanced NP uptake into Huh7.5 cells and NP could be considered as a promising delivery system for targeted treatment of hepatitis viruses.